DAMPAK PENGGUNAAN ROKOK ELEKTRIK VAPOR TERHADAP PRILAKU ANAK DAN PENDIDIKAN AGAMA SEBAGAI SOLUSI DI MADRASAH IBTIDAIYAH PERSMIN WONOKROMO SURABAYA - Muis, Muhammad; Nadlir, Nadlir (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2023)
Changes in children's behavior need to get serious attention from parents, teachers, and society. The environment, parenting, education, and religion influence the tendency to change behavior. The culture of imitating children to other people around them becomes a habit with no known good or deviant consequences. Problems arising from the impact of using e-cigarettes in schools need special handling; What changes in behavior occur due to the use of vapor e-cigarettes, and what are the solutions for religious education at MI Persmin. This type of research is qualitative with observation and interview data collection techniques. The collected data is classified, interpreted, analyzed, and conclusions are drawn. The results showed that MI Persmin's children did not know the effects of smoking vapor cigarettes on health, economy, and deviant behavior. Changes in the behavior of MI Persmin students caused by using vapor cigarettes include decreased motivation to study, likes to live extravagantly, and tend to underestimate religious practice. Therefore, religious education in schools, families, and communities is a solution to overcoming the adverse effects of using vapor cigarettes. The role of teachers and parents is very important as a guide and motivator in worship, habituation of morals, and positive behavior